Analisis Karakterisitik Geokimia Batugamping Menggunakan Metode X-Ray Difraction dan X-Ray Fluorescence di Kabupaten Buton Selatan Sulawesi Tenggara - ramadhan shaddad, Aqsal; Bakri, Hasbi (CV Insight Publisher, 2023)
Limestone is a sedimentary rock formed from calcium carbonate deposits and has a high content of calcium carbonate. It is used in the cement, fertilizer, glass, and construction industries. Research was conducted in the South Buton Regency, Southeast Sulawesi, using the geochimical methods of X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF). The aim of this study was to identify the minerals in limestone and analyze their geochemical characteristics. The research results showed the dominance of calcite minerals in the limestone of the area, with a high content of pure calcium carbonate (CaCO3). The study also observed the presence of other elements in the limestone. The analysis indicated low levels of elements such as Mg, CaF2, Ru2O, Fe2O3, Ag2O, and SrO. The XRD method was useful for mineral identification in limestone, while XRF analyzed the elemental content quantitatively. This research provides a deeper understanding of the mineral characteristics and composition of limestone in the South Buton Regency. This information is valuable for the development of the cement, fertilizer, glass, and construction industries. Additionally, the study also revealed the potential for other minerals in the limestone of the research area.